Back to the core: Alternative performance measurement - Davor Vasicek; Josip Cicak (UTMS Journal of Economics, 2019)
The reporting of alternative performance measures (APMs) is currently the focus of much debate in the world. In this paper, we analyse APMs basics, e.g. financial statements as the basis for alternative performance measurement. Accounting, with the basic concepts of documentation and verifiability, provides wide intervals of evaluation of all positions of all financial statements that have found economic expression in accounting policies. Using a variety of alternative accounting policies brings about different effects on the stated financial results and the value of the company. Each of the standard financial statements users has different information needs and their understanding of fair financial reporting. Which is why, APMs and financial ratios mustn't be basis for financial decisions without deep insight into the numbers from which ratios have been made. In this paper is given an overall literature review of accounting conservatism models, which should be used in assessment of bias in financial reporting.
Keywords: M41; 330; accounting; financial ratios; APMs; accounting conservatism